2015
DOI: 10.1007/s11482-015-9401-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Mental Health Effects of Social Isolation

Abstract: It is frequently hypothesized that feelings of social isolation are detrimental for an individual's mental health, however standard statistical models cannot estimate this effect due to reverse causality between the independent and dependent variables. In this paper we present endogeneity-corrected estimates of the mental health consequences of isolation (based on self-assessed loneliness scores) using Australian panel data. The central identification strategy comes from a natural source of variation where som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 44 publications
(49 reference statements)
3
54
0
Order By: Relevance
“…Separation from life ashore with months spent away from home and few opportunities for communication contribute to feelings of social isolation (explicitly discussed in [12] and [8]; see also Rhode et al [30] for isolation and loneliness and Shattell et al [31] and Apostolopoulos et al [32] for the social isolation of truckers). Besides direct reports of adverse effect on wellbeing other evidence gives support to the importance of social isolation as a challenge to seafarers' mental health.…”
Section: Deep-sea and Social Isolationmentioning
confidence: 99%
“…Separation from life ashore with months spent away from home and few opportunities for communication contribute to feelings of social isolation (explicitly discussed in [12] and [8]; see also Rhode et al [30] for isolation and loneliness and Shattell et al [31] and Apostolopoulos et al [32] for the social isolation of truckers). Besides direct reports of adverse effect on wellbeing other evidence gives support to the importance of social isolation as a challenge to seafarers' mental health.…”
Section: Deep-sea and Social Isolationmentioning
confidence: 99%
“…It is clear the latter view has value as it has been found that psychosocial factors are clearly implicated in the development, maintenance and recovery from CMHC (Dixon et al, ; Haslam, Jetten, Cruwys, Dingle, & Haslam, ). In particular, people with CMHC frequently experience social isolation and marginalisation (Corrigan, Markowitz & Watson, ; Rohde, D’Ambrosio, Tang, & Rao, ), which often worsens their symptoms (Topora et al, ; Wright, Gronfein & Owens, ). There is therefore a pressing need to develop evidence‐based social interventions to sustain wellbeing in adults experiencing CMHC (Johnson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, evidence shows that social isolation is a risk factor for mental illness (Rohde et al, ). Isolation gives rise to a depressive attribution style, where failures are attributed to internal, stable, or global causes (Cruwys et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During February 2020, BAO provided 76 counseling sessions and had 12 new clients initiate counseling services, while, in March 2020, BAO provided 110 counseling sessions and 16 new clients initiate counseling services. It is possible that this increase in counseling services is a result of the COVID-19 pandemic given that social isolation, a hallmark of the social distancing response required to slow the rate of new COVID-19 infections, has been linked to an increase in negative mental health outcomes such decreased wellbeing [5] and increased depression [6,7] and anxiety [7]. Employment disruption may also have a negative impact on mental health.…”
mentioning
confidence: 99%